Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/cod.12973
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial burden of hand eczema: Data from a European dermatological multicentre study

Abstract: This study identifies a specific psychological burden experienced by hand eczema patients, highlighting the need for focused psychosocial interventions. Physicians in particular should be aware of the need to identify anxiety and depression in female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 39 publications
(83 reference statements)
7
40
4
1
Order By: Relevance
“…Female patients probably had more distress related to limitations in work, leisure time, or domestic activities. Previous studies showed a considerable psychosocial burden of hand eczema and underline that anxiety and depression are more common in female patients . In this study we did not find an association between female sex and impairment of HRQoL in the QOLHEQ subdomain “emotions.” The regression analyses showed that lower “global satisfaction” was associated with more impairment of HRQoL; the standardized beta was −0.44, which indicates a moderate correlation.…”
Section: Discussioncontrasting
confidence: 72%
“…Female patients probably had more distress related to limitations in work, leisure time, or domestic activities. Previous studies showed a considerable psychosocial burden of hand eczema and underline that anxiety and depression are more common in female patients . In this study we did not find an association between female sex and impairment of HRQoL in the QOLHEQ subdomain “emotions.” The regression analyses showed that lower “global satisfaction” was associated with more impairment of HRQoL; the standardized beta was −0.44, which indicates a moderate correlation.…”
Section: Discussioncontrasting
confidence: 72%
“…Although not directly comparable, stress has been shown to be linked with a poor prognosis of other chronic dermatoses, such as AD, and the immunological reaction to psychological stress has been demonstrated to be altered in patients with AD, with stress modulating immunological mechanisms in ways that increase eczema severity . However, with regard to the severity of hand eczema, some studies did not find an association with stress, and as hand eczema is known to affect the psychological well‐being and quality of life of patients, it cannot be ruled out that persistence of hand eczema in itself may enhance stress levels and thereby strengthen the association of hand eczema and experienced stress.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] While there is a growing body of research on this topic, it is striking that almost all studies exploring the mental burden of skin diseases focused on assessing mental disorders. 2,[5][6][7] However, considering the World Health Organization's (WHO) definition of health as a 'state of well-being and not merely the absence of disease', 8 such studies are only able to provide a partial assessment of the full mental burden of skin diseases. Studies measuring mental health in terms of subjective well-being are almost absent in dermatologic research so far.…”
Section: Introductionmentioning
confidence: 99%